Analysis of Primary Iris and Ciliary Body Cysts in Chinese Patients With Primary Angle Closure Disease - Wei, Kun; Zuo, Chengguo; Xu, Jinyi; Chen, Liming; Wang, Dingqiao; Tang, Zhongshu; Lin, Mingkai (Frontiers in Medicine, 2021)
Aim To investigate the incidence and clinical features of primary iris and ciliary body cysts in Chinese primary angle closure disease (PACD). Patients were evaluated by measuring and analyzing the cysts with an ultrasound biomicroscope (UBM). Methods The data of patients diagnosed with PACD were reviewed. Demographic data were collected, and the cyst number, size, location, and trabecular-iris angle (TIA) were measured, with the size including the longest diameter (LD) and its corresponding vertical diameter (CVD). Results A total of 1334 cases (2317 eyes) were reviewed, and 409 cysts were found in 131 cases (168 eyes), with an average of 2.43 ± 3.14 cysts per eye. The ages of the patients with cysts ranged from 25 to 80 years, with an average age of 55.24 ± 12.22 years. The detection rate was 7.3%, and the majority of cysts were located in the iridociliary sulcus. Among the 131 patients, 94 had monocular cysts, while binocular cysts occurred in 37 patients. The locations of the cysts in both eyes were mainly in the inferior and temporal quadrants (42.5% and 34.0%, respectively). The cysts were mainly of medium size (49.9%), followed by small cysts (33.3%), large cysts (14.7%) and giant cysts (2.2%). The average LD was 0.68 ± 0.33 mm, and the average CVD was 0.45 ± 0.23 mm. There were no statistically significant differences in the TIA between the cyst area and unaffected area. Conclusions The incidence of cysts is approximately 7.3% in the PACD population. The cysts are mainly monocular, medium in size, and located in the iridociliary sulcus. Additionally, the cysts were located mainly in the inferior and temporal quadrants. These cysts have little effect on the anterior chamber angle.